Can a widely used stool pigment chart be used to triage patients for investigation of neonatal jaundice?. (29th September 2015) - Baker, A; Serra-Feliu, G; Akindolie, M; Vadamalayan, B; Arkely, C; Samyn, M; Sutcliffe, A
Abstract : National liver centres receive many referrals of infants with neonatal jaundice. Those with more severe cholestasis are at greater risk of having biliary atresia, benefitting from early surgery. While information on stool pigmentation is sought at referral, our experience is that it is not always correct. The authors therefore sent a covering letter with a stool pigment chart supplied by the Childrens' Liver Disease Foundation (CLDF) by first class post to the home or hospital where the child was resident and followed it up 1–2 days later by up to four telephone calls to record the colour of the stools assigned when they were compared to the chart. An admission date was assigned based on the referral information but if the stool colour proved to be pale on telephone inquiry a new date was assigned. 123 infants who were referred had charts sent. At referral 30 were stated to have pale stools, 66 pigmented stools and, in 27, pigment was unrecorded/unknown. Overall mean time from referral to admission was 10.1 days, range 0–25. Eighty-three parents and professionals (67.5%) who received the chart could be contacted. 24 graded the stools as pale by the CLDF chart and 59 as pigmented. In eight cases (9.6%) stools graded pale at original referral were actually pigmented, while in 10 cases (12%) a "normal" graded stool was reassessed as pale. These 10 proved to have non-specific neonatal hepatitis 4 (1 with intrahepatic calcifications), inspissated bile syndrome 2, biliary atresia, α-1-antitrypsin deficiency, hypopituitarism, shock liver 1 each. As a result of re-assessment, in 8 patients the admission date was considered early enough or the patient was too sick to travel earlier, but 16 patients were brought in a mean of 6.1 days earlier (range 1–23) with the case of BA brought in 7 days earlier. Referrals stating stool colour had only 67% sensitivity for pale stools. Use of a posted stool colour chart followed up by telephone calls can allow prioritisation of patients with pale stools to optimise treatment timelines and allow effective use of resources.